Earthfall - Walden, Mark (Walden, Mark. Earthfall trilogy, 2015)
When alien vessels arrive at Earth, countless people are taken -- save for Sam, a young man living in London. Within six months, Sam has begun to believe he is the only person left, but the discovery that there are other survivors launches Sam on a journey that will decide the fate of his world.